Physical activity and health - Blair, Steven N.; Bouchard, Claude; Haskell, William L. (Champaign, IL Human Kinetics, 2012)
The human body is designed for activity. For most of our history, physical activity was required for survival, but technological advances have eliminated much of the need for hard physical labor. As our activity levels have dropped, it has become clear that a physically inactive lifestyle can lead to a host of health problems. Physical Activity and Health, Second Edition, provides a comprehensive treatment of the research on the benefits of a physically active lifestyle in comparison with the harmful consequences of physical inactivity. Written by leading scientists from the United States, Canada, Europe, and Australia, Physical Activity and Health, Second Edition, brings together the results of the most important studies on the relationship between physical activity, sedentarism, and various health outcomes. The second edition has been fully updated based on the latest advances in this rapidly changing field and expanded to include the following new content: A chapter on the physiology of inactivity and the effects of sedentary behavior even in people who engage in appropriate amounts of physical activity, which is an area of growing interest; More extensive coverage of physical activity, aging, and the brain, including a new chapter on the relationship between physical activity and brain structures and functions; A chapter on the development of national and international physical activity and health guidelines, which will help readers better understand how scientific findings are converted into practical recommendations. Physical Activity and Health, Second Edition, offers a detailed yet concise presentation of key concepts as well as a framework to help readers relate results from single studies or collections of studies to the overall paradigm linking physical activity and physical fitness to health. For each of the topics covered, the text provides an overview of the most important research findings, discusses the limitations of the current knowledge base, and identifies directions for future investigation. At the core of the text is a review of our current understanding of how physical activity affects health concerns such as cardiovascular disease, diabetes, cancer, and obesity as well as aging and mental health. The text identifies sedentary living habits and poor fitness as major public health problems and examines the potential of physical activity to prevent disease and enhance quality of life. This complete resource also looks at the evolution of the field of physical activity and health; variations in physical activity levels across age, sex, and ethnic groups; the body's physiological responses to physical activity; dose-response issues; and the influence of genetics on physical activity, fitness, and health. The book ends with an integration of the issues covered and discusses new opportunities for research. The second edition of Physical Activity and Health continues to offer clear, user-friendly coverage of the most important concepts and research in the field. Numerous special features will aid readers in their comprehension of the material. Chapter outlines and callout boxes help readers key in on important topics and focus their reading, and chapter summaries, definitions of key terms, and study questions provide tools for review and self-testing. Where other books have simply promoted physical activity for the individual or a population, Physical Activity and Health, Second Edition, completely integrates current knowledge of the relationship between physical activity and health. With contributions from some of the finest scientists in the field, this comprehensive text offers information unmatched in accuracy and reliability.
Part I. History and Current Status of the Study of Physical Activity and Health -- Chapter 1. Why Study Physical Activity and Health? / Claude Bouchard, PhD; Steven N. Blair, PED; and William L. Haskell, PhD ; Human Evolution, History, and Physical Activity ; Burden of Chronic Diseases ; Health and Its Determinants ; Aging and Health ; Defining Physical Activity and Physical Fitness ; Physical Inactivity Versus Physical Activity ; Summary ; Review Materials -- Chapter 2. Historical Perspectives on Physical Activity, Fitness, and Health / Russell R. Pate, PhD ; Early Beliefs About Physical Activity and Health ; Scientific Inquiry on Exercise and Health ; Evolution of Physical Activity Guidelines ; Summary ; Review Materials -- Chapter 3. Physical Activity and Fitness With Age, Sex, and Ethnic Differences / Peter T. Katzmarzyk, PhD, FACSM ; Physical Activity ; Physical Fitness ; Summary ; Review Materials -- Chapter 4. Sedentary Behavior and Inactivity Physiology / Marc Hamilton, PhD; and Neville Owen, PhD ; Sedentary Behavior, Physical Activity, and Public Health ; Inactivity Physiology: The Underlying Biology of Acute and Chronic Muscular Inactivity ; Sedentary Behavior and Metabolic Health: Emerging Epidemiological Evidence ; Humans May Not Have Reached the Pinnacle of Physical Inactivity ; A Comprehensive Sedentary Behavior Research Agenda ; Public Health Implications ; Summary ; Review Materials -- Part II. Effects of Physical Activity on the Human Organism -- Chapter 5. Metabolic, Cardiovascular, and Respiratory Responses to Physical Activity / Edward T. Howley, PhD ; Relationship of Energy to Physical Activity ; Oxygen Consumption and Cardiovascular and Respiratory Responses to Exercise ; Effect of Training, Age, and Gender on Maximal Oxygen Uptake ; Application to Exercise Training and Physical Activity Interventions ; Summary ; Review Materials -- Chapter 6. Acute Responses to Physical Activity and Exercise / Adrianne E. Hardman, MSc, PhD ; Lipids and Lipoproteins ; Endothelial Function ; Insulin-Glucose Dynamics ; Blood Pressure ; Hematological Changes ; Immune Function and Inflammation ; Responses Related to Energy Balance ; Augmentation of Acute Effects by Training ; Summary ; Review Materials -- Chapter 7. Hormonal Response to Regular Physical Activity / Peter A. Farrell, PhD ; Defining Hormones ; Importance of Hormonal Regulation ; Regular Physical Activity and Hormonal Adaptations ; Summary ; Review Materials -- Chapter 8. Skeletal Muscle Adaptation to Regular Physical Activity / Howard J. Green, PhD ; Skeletal Muscle and Human Survival ; Muscle Cell: Composition, Structure, and Function ; Muscle Fiber Types and Subtypes ; Muscle Adaptation and Functional Consequences ; Aging Muscle: The Role of Training ; Summary ; Review Materials -- Chapter 9. Response of Liver, Kidney, and Other Organs and Tissues to Regular Physical Activity / Roy J. Shephard, MB, BS, MD (London), PhD, DPE ; Acute Effects of Physical Activity ; Chronic Effects of Physical Activity ; Strengths and Limitations of the Current Evidence ; Summary ; Review Materials -- Part III. Physical Activity, Fitness, and Health -- Chapter 10. Physical Activity, Fitness, and Mortality Rates / Michael J. LaMonte, PhD; and Steven N. Blair, PED ; Physical Activity and Mortality ; Fitness and Mortality ; Activity or Fitness and Mortality in Adults With Existing Diseases ; Quantifying the Population Mortality Burden of Inactivity ; Summary ; Review Materials -- Chapter 11. Physical Activity, Fitness, and Cardiac, Vascular, and Pulmonary Morbidities / Ian Janssen, PhD ; Low Physical Activity and Low Cardiorespiratory Fitness as Risk Factors for Cardiovascular Morbidities ; Low Physical Activity and Low Cardiorespiratory Fitness as Risk Factors for Pulmonary Morbidities ; Biological Mechanisms ; Role of Physical Activity in Patients with Cardiac, Vascular, and Pulmonary Morbidities ; Summary ; Review Materials -- Chapter 12. Physical Activity, Fitness, and Obesity / Robert Ross, PhD; and Ian Janssen, PhD ; Definition and Problem of Overweight and Obesity ; Fat Depots ; Relationships Among Excess Weight, Physical Activity, and Fitness ; Role of Physical Activity in Prevention and Treatment of Excess Weight ; Summary ; Review Materials -- Chapter 13. Physical Activity, Fitness, and Diabetes Mellitus / R. Jan-Willem Middelbeek, MD, MS; Oscar Alcazar, PhD; and Laurie J. Goodyear, PhD ; Diabetes: Definitions and Prevalence ; Epidemiology, Etiology, and Complications of Type 2 Diabetes ; Impact of Physical Activity on Insulin and Glucose Metabolism ; Epidemiological Evidence Indicating Benefits of Physical Activity in Preventing Type 2 Diabetes ; Summary of Randomized Controlled Trials on the Prevention of Type 2 Diabetes ; Importance of Regular Physical Activity for People With Type 2 Diabetes ; Summary ; Review Materials -- Chapter 14. Physical Activity, Fitness, and Cancer / I-Min Lee, MBBS, ScD ; Importance of Cancer ; How Physical Activity and Physical Fitness Decrease the Risk of Developing Cancer ; How We Study Whether Physical Activity and Physical Fitness Decrease the Risk of Developing Cancer ; Physical Activity, Physical Fitness, and Site-Specific Cancers ; Physical Activity and Cancer Survivors ; Summary ; Review Materials -- Chapter 15. Physical Activity, Fitness, and Joint and Bone Health / Jennifer Hootman, PhD, ATC, FACSM, FNATA ; Scientific Evidence ; Strengths and Limitations of the Evidence ; Summary ; Review Materials ; Chapter 16. Physical Activity, Muscular Fitness, and Health / Neil McCartney, PhD; and Stuart Phillips, PhD ; History of Resistance Training and Its Role in Health ; Fundamental Aspects of Resistance Training ; Resistance Training Throughout the Life Span ; Resistance Training in Disease and Disability ; Summary ; Review Materials -- Chapter 17. Physical Activity, Fitness, and Children / Thomas Rowland, MD ; Understanding the Exercise-Health Link in Children ; Defining the Kinds and Amount of Physical Activities for Health ; Optimal Intervention Strategies ; Biological Effects on Physical Activity in Youth ; Summary ; Review Materials -- Chapter 18. Risks of Physical Activity / Evert A.L.M. Verhagen, PhD; Esther M.F. van Sluijs, PhD; and Willem van Mechelen, MD, PhD / Risks of Physical Activity and Sport Participation ; Minimizing Risk and Maximizing Benefits ; Recommendations for Future Research ; Summary ; Review Materials -- Part IV. Physical Activity, Fitness, Aging, and Brain Functions -- Chapter 19. Physical Activity, Fitness, and Aging / Loretta DiPietro, PhD, MPH ; The Aging Process ; Methodological Considerations in Aging Research ; Demographics of Physical Activity Among Older Adults ; Dimensions of Physical Activity and Their Relationship to Health and Function in Aging ; Programmatic Issues in Promoting Physical Activity in Older Populations ; Summary ; Review Materials -- Chapter 20. Physical Activity and Brain Functions / Kirk I. Erickson, PhD ; Descriptive Questions ; Mechanistic Questions ; Applied Questions: Populations Benefiting From Physical Activity ; Moderating Questions: Factors Moderating the Effect of Physical Activity ; Summary ; Review Materials -- Chapter 21. Exercise and Its Effects on Mental Health / John S. Raglin, PhD; and Gregory S. Wilson, PED, FACSM ; Research Paradigms of Exercise and Mental Health Research ; Exercise and Depression ; Exercise and Anxiety ; Exercise and Schizophrenia ; Putative Mechanisms for the Psychological Benefits of Exercise ; Detrimental Psychological Responses to Exercise: The Overtraining Syndrome ; Summary ; Review Materials -- Part V. How Much Is Required and How Do We Get There? -- Chapter 22. Dose-Response Issues in Physical Activity, Fitness, and Health / William L. Haskell, PhD / Principles Guiding the Body's Response to Activity ; Components of the Physical Activity Dose ; Factors Determining Optimal Activity Dose ; Physical Activity and Fitness: Dose for Health Benefits ; Summary ; Review Materials -- Chapter 23. From Science to Physical Activity Guidelines / Mark S. Tremblay, PhD; and William L. Haskell, PhD ; Stages of Physical Activity Guideline Development ; Strengths, Limitations, and Challenges ; Summary ; Review Materials -- Part VI. New Challenges and Opportunities -- Chapter 24.
Includes bibliographical references
Keywords: Health; Exercise -- Physiological aspects; Physical fitness -- Health aspects